Leachate treatment using constructed wetland with magnetic field - Ahamad Nordin, Noor Ida Amalina (2006)
Leachate is one of the major problems to overcome in managing the landfill. Treatment that low cost, need less maintenance and environmental friendly are the target on how to treat the leachate. This research was focused on the capability of the magnetic technology to remove pollutant combined with constructed wetland. The study carried out through two type of systems, which were pre-treatment magnetic field with wetland (PTM-W) and continuous circulation magnetic field with wetland (CRM-W). A PTM-W system consists of two stages of treatments which are pretreatment using magnetic field (PTM) followed by treatment using wetland. The circulation flowrate for pre-treatment and CRM-W were fixed to 1.8 mL/s with exposure time of 6 hours fabricated from 6 paired of magnet with strength 0.55 Tesla. The constructed wetlands were planted with Eichhornia crassipes (floating type). The efficiency of the systems to reduce the concentration of orthophosphorus, nitrate nitrogen, ammonia nitrogen, BOD, COD, ferum and manganese were analysed, whilst, heavy metal uptakes was analyst in plant tissues. From the study it was found that the wetland is significantly contributed in removal efficiency of BOD, orthophosphorus and nitrate nitrogen. Circulation with magnet has the ability to reduce time of treatment in removal efficiency of COD, ammonia nitrogen, ferum and manganese. The results showed CRM-W systems can reduce up to 60% of ammonia nitrogen removal, 68.7 % of ferum and 60% of manganese after 6 hours of treatment). Wetland was able to remove 99% of nitrate nitrogen, 96% of ammonia nitrogen and 83% of BOD after end of experiment. It can be conclude that magnetic field posed a great role in removing heavy metal, whilst wetland has a great ability in removing orthophosphorus, nitrate nitrogen, ammonia nitrogen, BOD and COD.